Development of Authentic Assessment Instrument Based on Scientific Literacy to Measure Science Process Skills - Faizatul Mabruroh; M. Hasbi Ashsiddiqi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to develop an authentic assessment instrument based on scientific literacy to measure students' science process skills. Developing such instruments is significant as it ensures that assessments are more reflective of real-world scientific understanding and practices, potentially leading to improved educational practices. The development stages of this instrument use the research and development (RD) method with the 4D development model proposed by Sivasailam Thiagarajan, Dorothy S. Semmel, and Melyvn I. Semmel. The procedures for developing this instrument include four stages: definition, design, development, and dissemination. The research subjects were sixth-semester students in the Physics Education Study Program at UIN Raden Fatah Palembang who had taken Basic Physics and Thermodynamics courses. Using a purposive sampling technique, 15 students were involved, divided into three groups (low, medium, high) with five students in each group. The instruments developed were categorized as valid by experts, with a validity percentage of 90% for observation sheets and rubrics, 88% for performance assessment instruments, and 72% for authentic assessment experts. The response test was categorized as practical, with a percentage of 91%.